Soil Organic Carbon and Nitrogen Storage and Distribution in the Agricultural Soils as Affected by Soil Depths and Inundation Land Types: Soil Organic Carbon and Nitrogen Storage (Journal of the Asiatic Society of Bangladesh, Science, 2025)
A study was initiated on soil organic carbon (SOC) and total nitrogen (TN) storage and their distribution as affected by soil depths and inundation land types selecting ideal two catena across eight soil profiles up to the depth of 120 cm in the Brahmaputra and the Ganges alluviums. Soil organic carbon  and TN storage is higher in the surface soil depth than the other soil depths. The contents and distribution of SOC and TN in all the soil depths varies significantly. Moreover, inundation land types and soil depths exhibited a significant effect (p